MOFs (Metal-Organic Frameworks) derivative material with super-hydrophobic shell as well as preparation method and application of MOFs derivative material

By developing MOFs-derived materials with core-shell structures on MOFs materials, using graphite catalytic activity of iron metal centers, converting the shell into a highly graphitized carbon shell at high temperatures, solving the preparation of graphitized carbon materials in the prior art. The problem of high energy consumption and high cost has achieved an efficient and low energy consumption graphitization process, and a porous graphitized carbon material with superhydrophobic and excellent gas adsorption properties has been prepared.

CN119503799APending Publication Date: 2025-02-25GUANGDONG IND TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411650193.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art consumes a lot of energy and costs when preparing graphitized carbon materials, and it is difficult to achieve efficient graphitization at lower temperatures, affecting the performance and application of the material.

Method used

By developing MOFs-derived materials with core-shell structures based on MOFs materials, the graphite catalytic activity of the iron metal center is used to convert the shell into a highly graphitized carbon shell during high-temperature carbonization and activation treatment, while retaining multi-stage pore channels. structure.

Benefits of technology

Efficient graphitization at lower temperatures is achieved, and porous graphitized carbon materials with superhydrophobic properties and excellent gas adsorption properties are prepared, reducing energy consumption and improving the application prospects of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503799A_ABST
    Figure CN119503799A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of porous materials, and particularly relates to an MOFs derivative material with a super-hydrophobic shell and a preparation method and application thereof.The MOFs derivative material with the super-hydrophobic shell has the advantages that shell MOFs can be converted into a highly-graphitized carbon shell through a carbonization and activation process, meanwhile, a hierarchical porous structure is reserved and optimized inside, and the porous material with the super-hydrophobic shell is prepared; therefore, the MOFs derivative material with the super-hydrophobic property is successfully prepared. The super-hydrophobic shell layer not only enhances the moisture resistance of the material, but also can effectively improve the adsorption selectivity of gas molecules, and the internal hierarchical pore structure greatly increases the specific surface area of the material and provides rich active sites for adsorption of the gas molecules. The invention provides a novel efficient material for the field of gas adsorption and separation, and the unique structural characteristics and excellent performance of the material indicate that the material has wide application prospects in multiple fields such as high-purity gas preparation, environmental governance, energy storage and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of porous materials, and in particular relates to a MOFs derivative material with a super-hydrophobic shell, and a preparation method and application thereof. Background Art

[0002] VOCs (Volatile organic compounds) are volatile organic compounds, a common type of air pollutant. VOCs are important precursors to urban haze and photochemical smog, and are mainly derived from industries such as coal chemical industry, petrochemical industry, paint production, chemical fiber industry, metal coating, chemical coating, shoe and leather making, packaging and printing, daily necessities production, and tire manufacturing. The vast majority of VOCs have a foul or irritating odor, which can cause sensory discomfort when in contact with the human body, seriously affecting people's quality of life. VOCs have complex ingredients and special odors, and are toxic, irritating, teratogenic, and other carcinogenic effects. VOCs and the semi-volatile organic compounds they form in the atmosphere will cause photochemical pollution and eventually form ozone and PM2.5.

[0003] Graphitized carbon has broad development and research prospects in the field of VOCs adsorption due to its large pore size, good hydrophobicity, high thermal stability and adsorption performance, and strong desorption and regeneration ability. The traditional method of preparing graphitized carbon requires high temperature conditions, generally above 2000°C. Although this method can synthesize graphitized carbon, the reaction process consumes a lot of energy and is costly. However, graphitization is a solid-phase reaction from an amorphous state to a crystalline state. This transformation resistance is very large and it is easy to form a metastable state. Therefore, carbon is not easy to graphitize. In order to reduce the energy barrier during graphite conversion and save energy consumption, by adding a certain metal, metal compound or non-metal and its compound and heating it, it is possible to graphitize at a lower temperature than that required for normal graphitization, and the degree of graphitization can be increased. Therefore, catalytic graphitization is widely used. At present, there are many catalysts with catalytic graphitization functions reported, such as Fe, Co, Ni, B, Si, Ti, Mn and other metal elements, metal oxides or metal compounds, which have a good catalytic graphitization effect on carbon materials.

[0004] Metal Organic Frameworks (MOFs), as an emerging family of porous functional materials, are mainly zeolite-like framework materials formed by self-assembly of metal ions and organic ligands. In recent years, the preparation of porous carbon materials using MOF materials as precursors or templates has become a hot topic of research. The reasons are: (1) The abundant organic ligands in MOF materials can provide carbon sources for carbonization; (2) Removing metal ions during or after carbonization will give the porous carbon materials a greater porosity; (3) The porous skeleton structure of MOF can act as a hard template, thereby introducing additional carbon sources to prepare high-quality porous carbon materials. In addition, MOFs materials can also be used as graphite catalyst precursors. Therefore, it is obviously of great significance to develop new porous graphitized carbon materials with high-efficiency VOCs adsorption performance, superhydrophobic properties and good regeneration ability based on MOFs materials. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a MOFs-derived material with a superhydrophobic shell and a preparation method and application thereof, which provides a new type of high-efficiency material for the field of gas adsorption and separation. Its unique structural characteristics and excellent performance indicate that it has broad application prospects in many fields such as high-purity gas preparation, environmental governance, and energy storage.

[0006] To achieve the above object, the present invention provides a method for preparing a MOFs-derived material having a super-hydrophobic shell, comprising the following steps:

[0007] (1) Al(NO3) 3. 9H2O and sodium acetate were dissolved in deionized water, stirred for reaction, and then centrifuged and dried to obtain aluminum metal clusters;

[0008] (2) dispersing the aluminum metal clusters prepared in step (1), Fe(NO3)3.9H2O and trimesic acid in deionized water, adding SAPO-34 molecular sieves, and dripping acetic acid, stirring evenly, transferring the mixed solution into a stainless steel high-pressure reactor, and performing hydrothermal synthesis to obtain a reaction product;

[0009] (3) centrifuging the reaction product obtained in step (2), rinsing with ethanol and vacuum drying to obtain a core-shell MOFs composite material;

[0010] (4) dispersing the core-shell MOFs composite material obtained in step (3) and the additional carbon source in deionized water, and then subjecting the mixed system to centrifugation, high-temperature carbonization and activation treatment in sequence to obtain an activated product;

[0011] (5) The activated product obtained in step (4) is sequentially subjected to acid washing, water washing and vacuum drying to obtain the MOFs-derived material having a super-hydrophobic shell.

[0012] Further, in step (1), the Al(NO3) 3. The mass ratio of 9H2O, sodium acetate and deionized water is (1.8-2.5):1:(15-20).

[0013] Furthermore, in step (1), the stirring reaction is carried out at room temperature for 5 to 10 hours.

[0014] Furthermore, in step (2), the mass ratio of the aluminum metal cluster, Fe(NO3)3.9H2O, trimesic acid, SAPO-34 molecular sieve, acetic acid and deionized water is (1.5-3):1:(1.6-2.7):(0.1-0.2):(1-2):(30-60).

[0015] Furthermore, in step (2), the hydrothermal synthesis is carried out at 150-180° C. for 5-10 hours.

[0016] Furthermore, in step (3), the ethanol immersion is performed 2 to 4 times, the duration of each ethanol immersion is 8 to 15 hours, and the vacuum drying is performed at 120 to 150° C. for 8 to 12 hours.

[0017] Furthermore, in step (4), the additional carbon source is glucose, the mass mixing ratio of the core-shell MOFs composite material to the additional carbon source is 1:3-6, the high-temperature carbonization is to heat the temperature to 500-700°C at a heating rate of 5°C / min under continuous nitrogen flow, maintain for 3 hours and obtain a carbonized product, the activation treatment is to heat the carbonized product and the activator to 700-800°C at a heating rate of 5°C / min under nitrogen protection, maintain for 0.5-1.5 hours, and the ratio of the carbonized product to the activator potassium hydroxide is 1:3.

[0018] Furthermore, the vacuum drying in step (5) is vacuum drying at 120-150° C. for 8-12 hours.

[0019] The present invention also provides a MOFs derivative material having a super-hydrophobic shell prepared by the preparation method.

[0020] The present invention also provides an application of the MOFs-derived material with a super-hydrophobic shell in gas adsorption and separation.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] The present invention proposes an innovative preparation method, using a core-shell MOFs composite material as a precursor and template. The key to the core-shell MOFs composite material is that its shell portion contains an iron metal center with graphite catalytic activity, and this property plays an important role in the subsequent carbonization process. Through the carbonization activation process, the shell MOFs can be converted into a highly graphitized carbon shell, while the multi-level pore structure is retained and optimized internally, thereby successfully preparing a MOFs derivative material with super-hydrophobic properties. This super-hydrophobic shell not only enhances the moisture resistance of the material, but also effectively improves the adsorption selectivity of gas molecules, while the internal multi-level pore structure greatly increases the specific surface area of ​​the material, providing abundant active sites for the adsorption of gas molecules. The MOFs derivative material with a super-hydrophobic shell provided by the present invention and its preparation method provide a new type of high-efficiency material for the field of gas adsorption and separation. Its unique structural characteristics and excellent performance indicate that it has broad application prospects in many fields such as high-purity gas preparation, environmental governance, and energy storage.

[0023] The MOFS-derived material with a superhydrophobic shell prepared by the present invention exhibits several significant advantages: first, it has a rich multi-level pore structure inside, which not only provides a broad adsorption space for gas molecules, but also promotes the rapid diffusion of gas molecules inside the material; second, the presence of a highly graphitized carbon shell effectively reduces the material's adsorption of water molecules and improves the adsorption selectivity of gas molecules, thereby giving the material excellent gas adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 N2 adsorption-desorption isotherms of MOFs-derived materials prepared in Examples 1-4 of the present invention;

[0026] Figure 2 This is a TEM image of the MOFs-derived material prepared in Example 1 of the present invention, wherein the scale is 5 nm;

[0027] Figure 3 This is a water contact angle diagram of the MOFs-derived material prepared in Example 1 of the present invention;

[0028] Figure 4 This is the adsorption isotherm diagram of benzene by the MOFs-derived material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0030] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0033] The terms "include", "comprising", "having", "containing" and the like used herein are all open-ended terms, which mean including but not limited to. The room temperature described below is 25°C.

[0034] The present invention provides a method for preparing a MOFs-derived material having a super-hydrophobic shell, comprising the following steps:

[0035] (1) Al(NO3) 3. 9H2O and sodium acetate were dissolved in deionized water, stirred at room temperature for 5-10 hours, centrifuged at 4000-8000 r / min for 5-15 minutes, and dried to obtain aluminum metal clusters; wherein Al(NO3) 3. The mass ratio of 9H2O, sodium acetate and deionized water is (1.8-2.5):1:(15-20);

[0036] (2) Aluminum metal clusters, Fe(NO3)3.9H2O and trimesic acid are dispersed in deionized water, SAPO-34 molecular sieves are added, and acetic acid is added dropwise. After stirring evenly, the mixed solution is transferred into a stainless steel high-pressure reactor and hydrothermally synthesized at 150-180°C for 5-10 hours; wherein the mass ratio of aluminum metal clusters, Fe(NO3)3.9H2O, trimesic acid, SAPO-34 molecular sieves, acetic acid and deionized water is (1.5-3):1:(1.6-2.7):(0.1-0.2):(1-2):(30-60);

[0037] (3) centrifuging the reaction product of step (2), then rinsing it with ethanol for 2 to 4 times for 8 to 15 hours at room temperature, and then vacuum drying it at 120 to 150° C. for 8 to 12 hours to obtain a core-shell MOFs composite material;

[0038] (4) dispersing the composite material obtained in step (3) and the additional carbon source glucose in deionized water at a mass mixing ratio of 1:3-6, then centrifuging the mixed system, and then heating to 500-700°C at a heating rate of 5°C / min and maintaining for 3 hours under continuous nitrogen flow for high-temperature carbonization, and then performing an activation treatment to obtain an activated product; wherein the activation treatment is to heat the carbonized product and the activator potassium hydroxide at a ratio of 1:3 under nitrogen protection at a heating rate of 5°C / min to 700-800°C, and maintain for 0.5-1.5 hours;

[0039] (5) The activated product obtained in step (4) is sequentially acid-washed, water-washed and vacuum-dried at 120-150° C. for 8-12 h to obtain a MOFs-derived material having a superhydrophobic shell.

[0040] The present invention will be further described in detail below in conjunction with specific embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0041] Example 1

[0042] Embodiment 1 of the present invention provides a method for preparing a MOFs-derived material having a super-hydrophobic shell, comprising the following steps:

[0043] 4.091gAl(NO3) 3.9H2O and 1.852g sodium acetate were dissolved in 35mL deionized water, stirred at room temperature for 8h, centrifuged at 5000r / min for 10min, and dried to obtain aluminum metal clusters. Then 2.895g aluminum metal clusters, 1.025g Fe(NO3)3.9H2O, and 1.680g trimesic acid were dispersed in 50mL deionized water, 0.135g SAPO-34 molecular sieves were added, and 2mL acetic acid was added dropwise. After stirring evenly, the resulting mixed solution was transferred into a stainless steel autoclave and heated at 160°C for 8h. After that, the product was centrifuged, washed with ethanol at room temperature twice, each time for 8h, and then vacuum dried at 120°C for 10h to obtain a core-shell MOFs composite material.

[0044] 1.0g of core-shell MOFs composite material and 4.0g of glucose carbon source were dispersed in 15mL of deionized water, and the mixture was stirred evenly, centrifuged and placed in a tube furnace, and heated to 700℃ at 5℃ / min for 3h under nitrogen protection. The carbonized sample was added with KOH (carbonized sample / KOH=1:3), mixed evenly, and placed in a tube furnace, and heated to 800℃ at 5℃ / min for 1h under nitrogen protection, and then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 8h to obtain a MOFs derivative material with a superhydrophobic shell.

[0045] Example 2

[0046] Embodiment 2 of the present invention provides a method for preparing a MOFs-derived material having a super-hydrophobic shell, comprising the following steps:

[0047] 4.090gAl(NO3) 3. 9H2O and 2.272g sodium acetate were dissolved in 45mL deionized water, stirred at room temperature for 10h, centrifuged at 8000r / min for 5min, and dried to obtain aluminum metal clusters. Then 1.540g aluminum metal clusters, 1.027g Fe(NO3)3.9H2O, and 1.643g trimesic acid were dispersed in 30mL deionized water, 0.103g SAPO-34 molecular sieves were added, and 1mL acetic acid was added dropwise. After stirring evenly, the resulting mixed solution was transferred into a stainless steel autoclave and heated at 150°C for 10h. After that, the product was centrifuged, washed with ethanol at room temperature twice, each time for 15h, and then vacuum dried at 120°C for 12h to obtain a core-shell MOFs composite material.

[0048] 1.0g of core-shell MOFs composite material and 3.0g of glucose carbon source were dispersed in 15mL of deionized water, and the mixture was stirred evenly, centrifuged and placed in a tube furnace, and heated to 500℃ at 5℃ / min for 3h under nitrogen protection. The carbonized sample was added with KOH (carbonized sample / KOH=1:3), mixed evenly, and placed in a tube furnace, and heated to 700℃ at 5℃ / min for 1.5h under nitrogen protection, and then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 8h to obtain a MOFs derivative material with a superhydrophobic shell.

[0049] Example 3

[0050] Embodiment 3 of the present invention provides a method for preparing a MOFs-derived material having a super-hydrophobic shell, comprising the following steps:

[0051] 4.090gAl(NO3) 3. 9H2O and 1.636g sodium acetate were dissolved in 25mL deionized water, stirred at room temperature for 5h, centrifuged at 4000r / min for 15min, and dried to obtain aluminum metal clusters. Then 3.045g aluminum metal clusters, 1.015g Fe(NO3)3.9H2O, and 2.740g trimesic acid were dispersed in 60mL deionized water, 0.205g SAPO-34 molecular sieves were added, and 2mL acetic acid was added dropwise. After stirring evenly, the resulting mixed solution was transferred into a stainless steel autoclave and heated at 180°C for 5h. After that, the product was centrifuged, washed with ethanol at room temperature for 4 times, each time for 8h, and then vacuum dried at 150°C for 8h to obtain a core-shell MOFs composite material.

[0052] 1.0g of core-shell MOFs composite material and 6.0g of glucose carbon source were dispersed in 15mL of deionized water, and the mixture was stirred evenly, centrifuged and placed in a tube furnace, and heated to 600℃ at 5℃ / min for 3h under nitrogen protection. The carbonized sample was added with KOH (carbonized sample / KOH=1:3), mixed evenly, and placed in a tube furnace, and heated to 800℃ at 5℃ / min for 0.5h under nitrogen protection, and then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 8h to obtain a MOFs derivative material with a superhydrophobic shell.

[0053] Example 4

[0054] Embodiment 4 of the present invention provides a method for preparing a MOFs-derived material having a super-hydrophobic shell, comprising the following steps:

[0055] 4.090gAl(NO3) 3.9H2O and 1.636g sodium acetate were dissolved in 25mL deionized water, stirred at room temperature for 5h, centrifuged at 4000r / min for 15min, and dried to obtain aluminum metal clusters. Then 2.037g aluminum metal clusters, 1.005g Fe(NO3)3.9H2O, and 2.740g trimesic acid were dispersed in 50mL deionized water, 0.155g SAPO-34 molecular sieves were added, and 2mL acetic acid was added dropwise. After stirring evenly, the resulting mixed solution was transferred into a stainless steel autoclave and heated at 160°C for 6h. After that, the product was centrifuged, washed with ethanol at room temperature twice, each time for 8h, and then vacuum dried at 150°C for 8h to obtain a core-shell MOFs composite material.

[0056] 1.0g of core-shell MOFs composite material and 5.0g of glucose carbon source were dispersed in 15mL of deionized water, and the mixture was stirred evenly, centrifuged and placed in a tube furnace, and heated to 500℃ at 5℃ / min for 3h under nitrogen protection. The carbonized sample was added with KOH (carbonized sample / KOH=1:3), mixed evenly, and placed in a tube furnace, and heated to 800℃ at 5℃ / min for 1h under nitrogen protection, and then washed with 1mol / L hydrochloric acid and water, and finally dried at 150℃ in vacuum for 8h to obtain a MOFs derivative material with a superhydrophobic shell.

[0057] Test Example 1

[0058] The pore structure of the MOFs-derived material prepared in the example was characterized using a three-station fully functional multi-purpose adsorption instrument 3Flex produced by Micromertics, USA. The results are shown in Table 1.

[0059] Table 1 Pore structure parameters of MOFs derived materials prepared in Example

[0060]

[0061] As can be seen from Table 1, the specific surface area of ​​the MOFs-derived material with super-hydrophobic shell prepared by the method of the present invention can reach 1589-1886 m 2 / g, with a total pore volume of 0.76-1.16cm 3 / g, indicating that the glucose-based porous carbon material prepared by the present invention has a large specific surface area and a high porosity.

[0062] Figure 1 is the N2 adsorption-desorption isotherm of the MOFs-derived materials prepared in Examples 1-4 of the present invention, Figure 1It can be seen that the MOFs-derived materials prepared in Examples 1-4 of the present invention have a rapidly increasing adsorption of N2 at relatively low pressures as the pressure increases, indicating that they have a rich microporous structure. The adsorption amount increases slowly with the increase in pressure and a small hysteresis loop appears, indicating that the material has a medium- and macro-porous structure, indicating that the prepared MOFs-derived porous carbon material has a rich multi-level pore structure and a high specific surface area.

[0063] Figure 2 TEM image of the MOFs-derived material prepared in Example 1 of the present invention, Figure 2 It can be seen that the shell layer of the MOFs-derived material prepared in Example 1 of the present invention has an obvious graphitized carbon layer structure.

[0064] Figure 3 The water contact angle of the MOFs-derived material prepared in Example 1 of the present invention is given by Figure 3 It can be seen that the water contact angle of the MOFs-derived material prepared in Example 1 of the present invention is 136.1°, indicating that it has super hydrophobicity.

[0065] Figure 4 is the adsorption isotherm of benzene by the MOFs-derived material prepared in Example 1 of the present invention, Figure 4 It can be seen that the adsorption amount of benzene by the MOFs derivative material prepared in Example 1 of the present invention can reach 12.5 mmol / g. The above shows that the MOFs derivative material with a superhydrophobic shell is successfully prepared by the method of the present invention, and exhibits excellent adsorption performance for benzene.

[0066] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a MOFs-derived material having a super-hydrophobic shell, characterized in that: The following steps are involved: (1) Al(NO3) 3. 9H2O and sodium acetate were dissolved in deionized water, stirred for reaction, and then centrifuged and dried to obtain aluminum metal clusters; (2) dispersing the aluminum metal clusters prepared in step (1), Fe(NO3)3.9H2O and trimesic acid in deionized water, adding SAPO-34 molecular sieves, and dropping acetic acid, stirring evenly, transferring the mixed solution into a stainless steel high-pressure reactor, and performing hydrothermal synthesis to obtain a reaction product; (3) centrifuging the reaction product obtained in step (2), rinsing with ethanol and vacuum drying to obtain a core-shell MOFs composite material; (4) dispersing the core-shell MOFs composite material obtained in step (3) and the additional carbon source in deionized water, and then subjecting the mixed system to centrifugation, high-temperature carbonization and activation treatment in sequence to obtain an activated product; (5) The activated product obtained in step (4) is sequentially subjected to acid washing, water washing and vacuum drying to obtain the MOFs-derived material having a super-hydrophobic shell.

2. The preparation method according to claim 1, characterized in that: In step (1), the Al(NO3) 3. The mass ratio of 9H2O, sodium acetate and deionized water is (1.8-2.5):1:(15-20).

3. The preparation method according to claim 1, characterized in that: In step (1), the stirring reaction is carried out at room temperature for 5 to 10 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the aluminum metal cluster, Fe(NO3)3.9H2O, trimesic acid, SAPO-34 molecular sieve, acetic acid and deionized water is (1.5-3):1:(1.6-2.7):(0.1-0.2):(1-2):(30-60).

5. The preparation method according to claim 1, characterized in that: In step (2), the hydrothermal synthesis is carried out at 150-180° C. for 5-10 hours.

6. The preparation method according to claim 1, characterized in that: In step (3), the ethanol immersion is performed 2 to 4 times, and the duration of each ethanol immersion is 8 to 15 hours. The vacuum drying is performed at 120 to 150° C. for 8 to 12 hours.

7. The preparation method according to claim 1, characterized in that: In step (4), the additional carbon source is glucose, the mass mixing ratio of the core-shell MOFs composite material to the additional carbon source is 1:3-6, the high-temperature carbonization is to heat the temperature to 500-700°C at a heating rate of 5°C / min under continuous nitrogen flow, maintain for 3 hours and obtain a carbonized product, the activation treatment is to heat the carbonized product and the activator to 700-800°C at a heating rate of 5°C / min under nitrogen protection, maintain for 0.5-1.5 hours, and the ratio of the carbonized product to the activator potassium hydroxide is 1:

3.

8. The preparation method according to claim 1, characterized in that: The vacuum drying in step (5) is performed at 120 to 150° C. for 8 to 12 hours.

9. A MOFs-derived material having a super-hydrophobic shell prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the MOFs-derived material with a superhydrophobic shell as claimed in claim 9 in gas adsorption and separation.